Methamphetamine use alters human plasma extracellular vesicles and their microRNA cargo: An exploratory study. Issue 1 (28th November 2020) - Sandau, Ursula S.; Duggan, Erika; Shi, Xiao; Smith, Sierra J.; Huckans, Marilyn; Schutzer, William E.; Loftis, Jennifer M.; Janowsky, Aaron; Nolan, John P.; Saugstad, Julie A.
Abstract: Methamphetamine (MA) is the largest drug threat across the globe, with health effects including neurotoxicity and cardiovascular disease. Recent studies have begun to link microRNAs (miRNAs) to the processes related to MA use and addiction. Our studies are the first to analyse plasma EVs and their miRNA cargo in humans actively using MA (MA‐ACT) and control participants (CTL). In this cohort we also assessed the effects of tobacco use on plasma EVs. We used vesicle flow cytometry to show that the MA‐ACT group had an increased abundance of EV tetraspanin markers (CD9, CD63, CD81), but not pro‐coagulant, platelet‐, and red blood cell‐derived EVs. We also found that of the 169 plasma EV miRNAs, eight were of interest in MA‐ACT based on multiple statistical criteria. In smokers, we identified 15 miRNAs of interest, two that overlapped with the eight MA‐ACT miRNAs. Three of the MA‐ACT miRNAs significantly correlated with clinical features of MA use and target prediction with these miRNAs identified pathways implicated in MA use, including cardiovascular disease and neuroinflammation. Together our findings indicate that MA use regulates EVs and their miRNA cargo, and support that further studies are warranted to investigate their mechanistic role in addiction, recovery, and recidivism.